Pengaruh Ketidak Bebasan Anak Dalam Bermain - Kharisma Febilda Rahayu; Ahmad Fauzan Azima (Jurnal Riset Multidisiplin Edukasi, 2025)
This research examines the phenomenon of children's play deprivation in Indonesia, characterized by declining play freedom due to technological advances, changing parenting approaches, urbanization, and safety concerns. The study aims to analyze manifestations and causative factors of play deprivation, identify its multidimensional impacts, evaluate intervention effectiveness, and formulate evidence-based recommendations. A qualitative library research method was employed by analyzing recent literature (2020-2025) from national and international databases. Results show play restrictions manifest in physical, temporal, and structural forms, with Indonesian children spending 5.2 hours daily on digital activities. Impacts include reduced motor capacity (27% lower), creativity deficits (31%), interpersonal difficulties, and increased mental health risk. Intervention programs like "Free Play Space" demonstrated a 47% increase in free play activities. The study concludes that an integrated multi-stakeholder approach based on the "Managed Risk" paradigm is necessary to balance safety and freedom in children's play.